(untitled) (FULafia Journal of Science and Technology, 2019)
A study of myriads of chemical pollutants in aquatic environment was carried out from the effluent of Nottingham Sewage Treatment Works (STWs) in United Kingdom. Using a solid phase extraction - gas chromatography technique (SPE-GCMS), fifteen compounds detected in sampled STW effluents ranged between 1.1 - 33.5 ng L-1 with percentage recoveries of 78.6 – 97.8%. The most abundant compounds found in the final effluent were nicotine, ibuprofen, codeine, ephedrine, procaine, benzoylecgonine, lidocaine, and caffeine, with mean concentrations of 21.4 ± 6.4, 16.7± 4.8, 15.1 ± 6.3, 10.1 ± 3.9, 9.1 ± 3.4, 5.6 ± 3.1, 5.3 ± 5.2 and 5.2 ± 1.9 ng L-1, respectively. The instrumental limits of detection (LODs) from 0.1 – 1.7 ng L-1, with standard deviations (STDs) of 1.1– 21.4% for all the compounds were also observed. The levels of illicit drugs and abused pharmaceuticals detected from the effluents showed the occurrence of these drugs and the Nottingham STW as one of the main transport routes to the receiving environment. These findings have further shown that chemicals in effluent get to the environment due to their incomplete removal from the STW. Persistence influx of these pollutants into the aquatic environment may have implication on ecosystems.